Morigo Stick: Pelatihan Pemanfaatan Daun Kelor Sebagai Snack Sehat untuk Meningkatkan Gizi dan Mencegah Stunting di Desa Gumuksari - Elysia, Amanda Putri; Ariyani, Vinna; Fatmawati, Cici Lia Ayu; Anggraeni, Cindy Dewi; Ikhwantari, Regita Dyah; Sanaya, Nova Nabila Ayu; Triyandini, Tarisa; Fitria, Nia Nur Afni; Hermawaty, Alvina; Wicaksono, Iwan (Jurnal Pengabdian Masyarakat, 2025)
Stunting is a chronic nutritional problem that is still prevalent in Gumuksari Village due to low nutritional knowledge and limited access to nutritious food. Moringa leaves (Moringa oleifera) were chosen as a solution because of their high nutritional content and ease of cultivation in the local area. This community service aims to improve public knowledge of nutrition while introducing innovations in processing Moringa leaves into healthy snacks as an alternative nutritious food to prevent stunting. The implementation method consists of three stages: (1) socialization on the importance of nutrition and the dangers of stunting, (2) training in making Moringa-based snacks, including demonstrations and practice assistance, and (3) evaluation through pre-test and post-test of knowledge and group discussions. The results of the activity showed a significant increase in participants’ understanding of nutrition (from 45% to 82%) and enthusiasm for producing the snack. As many as 75% of participants committed to developing the product independently. This activity proves that empowering communities through the utilization of local ingredients such as Moringa leaves can be a sustainable solution to improve food and nutrition security, especially in efforts to prevent stunting in rural areas.